The Johnson Years, Volume Two Vietnam, the Environment, and Science - Divine, Robert A. (University Press of Kansas, 1987)
Stretching from November 1963 to January 1969, the administration of Lyndon Baines Johnson was marked both by division and tumult and by significant accomplishments. In this volume, Robert Divine has brought together seven senior scholars who, in new essays, explore aspects of domestic and foreign policy during the Johnson years. This collection is a sequel to Divine's earlier volume (originally published as Exploring the Johnson Years).The seven essays that compose Volume Two, together with Divine's incisive and perceptive historiographical overview, offer new insights into Johnson's complex character and leadership style. The LBJ that emerges from these pages is a very human figure who understands the corrosive, pervasive impact of the Vietnam War on his administration and who struggles to try to preserve the domestic programs he fought so long and hard to achieve.In exploring the antiwar movement, tax and foreign economic policies, environmental and health care questions, and the space program, these essays demonstrate how domestic issues were critically affected by the Vietnam War and provide a fuller understanding of Johnson's vital but flawed legacy to the nation.